Financing Devolution in a COVID-19 Environment: The Status of Devolution in Zimbabwe - Mujeni, Ruvarashe Chigiya (Quest Journal of Management and Social Sciences, 2021)
Background: The concept of devolution has always presented significant controversy in African unitary states. It is often viewed with inherent suspicion and skepticism based on the lack of mutual trust between the people and the government. While proponents see it as a form of empowerment, resistant groups in society view the decentralization of government powers and responsibilities as a gateway to success. Despite the devolution agenda being a major component of local governance in the Zimbabwean Constitution of 2013, it would not be practically implemented until the new dispensation that rose into power in 2018. However, the coming in of the COVID-19 pandemic has significantly marred the take-off of devolution implementation in Zimbabwe. Whilst COVID-19 cases continue to escalate on the globe, African countries continue to battle not only with the second wave of the pandemic but also with the new COVID-19 variants. Already fragile economies of these countries, the governments were forced to prioritize the national budgets in response to the pandemic; consequently, other social and developmental issues were left behind. Objective: This study discusses the contemporary status of devolution in Zimbabwe to ascertain the extent of implementation; provide supportive legislation for devolution structures through recommendations; analyze devolution disbursements from 2019 before COVID-19 to date; assess the local authorities’ initial requests versus the disbursements in 2019 and 2020. Method: The researcher carried out a desk review and followed the principles of case study design by analyzing financial statements, reports and data coming in from the Councils and relevant Government ministries. The meaning was also derived by critically reviewing, organizing and interpreting related information from books and articles published in newspapers and journals. Result: Despite Section 264(1) of the Constitution providing for devolution of power to the three tiers of the Government, there is no supporting legislature in place as yet to actualize this key element. The Government Budgetary Allocation of 5% is not meeting local authority demands. Conclusion: The onset of the COVID-19 pandemic in late 2019 reduced the pace of the devolution process because the funds were channeled to fight against the virus. If properly practiced, devolution may be one of the solutions to the development of the Zimbabwean economy since the devolution program is largely founded on the principle of empowering provincial government councils and Local Authorities to spearhead economic and social development projects in their areas by leveraging on local resources. It may also solve issues of corruption in many local councils in Zimbabwe by improving accountability mechanisms, especially where sub governments are permitted to progressively compete with each other to establish innovative ways of delivering public services efficiently and inexpensively. Implications: The findings imply that the Government policies can affect the social and economic well-being of citizens, however, the COVID-19 pandemic has far outweighing impacts. Secondly, the coronavirus outbreak has proved how much the Government of Zimbabwe is ill-prepared to deal with a pandemic of this dimension. Policymakers should ensure that finances are set in the national budget for unseen events so as not to derail other Government projects. Originality: This paper is original and not sent anywhere for publication.